The promises and perils of central bank digital currencies - Louis Larue; Clément Fontan; Joakim Sandberg (Revue de la Régulation)
This paper analyzes the proposal that central banks should issue digital currencies (CBDC) to provide a public alternative to private digital accounts and cryptocurrencies. We build on some recent themes in political economy research to give a broader and more balanced perspective than the existing literature, highlighting both the promises and perils of CBDC. We argue that, on the one hand, the present state of the private financial sector is problematic and regulators should seek to tackle the issues of financial power, financial instability and lack of adequate monetary policy options. On the other hand, implementing CBDC comes with risks of its own, such as that of creating a “Frankenstein scenario” where too much power is given to unelected technocrats. Our tentative conclusion is therefore that CBDC should be seen as a second-best option, while the primary focus of policy makers should be on the possibility of financial re-regulation.